Referral, Identification, and Retention of Underrepresented Gifted Students - Hemingway, Saana (International Journal for Talent Development and Creativity, 2022)
Research shows that the percentage of Culturally and Linguistically Different (CLD) students identified for participation in gifted education programs does not correlate with the percentage of minority students in the classroom. Black and Brown students are underserved and underrepresented in gifted programs and Advanced Placement classes, when compared to their White and Asian peers. CLD gifted students are at a greater risk for underachievement, dropping out of school, and incarceration. This article review focuses on referral, identification and retention of CLD students to address the problem of underrepresentation in gifted education. The central argument is that the referral process and identification for gifted students must be culturally and linguistically sensitive and teacher training must be incorporated into professional development to achieve this goal. Once students are identified as gifted, culturally sensitive gifted programs must be utilized to increase retention.